1977
DOI: 10.1172/jci108767
|View full text |Cite
|
Sign up to set email alerts
|

The Measurement of Apolipoprotein A-I and A-II Levels in Men and Women by Immunoassay

Abstract: A B S T R A C T To study apolipoprotein A-II, a simple, precise, and accurate immunodiffusion assay was developed and applied in a population sample of industrial employees. Apolipoprotein A-II (A-II) did not increase with age in men (r = -0.20, n = 172), but showed a slight increase with age in women (0.1 mg/dl per yr, r = 0.20, n = 188). A-II correlated significantly with apolipoprotein A-I (A-I) (r = 0.71) and high density lipoprotein (HDL) cholesterol (men, r = 0.64; women, r = 0.49). The A-I/A-II ratio wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
84
0
1

Year Published

1982
1982
2002
2002

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 375 publications
(92 citation statements)
references
References 27 publications
7
84
0
1
Order By: Relevance
“…14 ApoA-I concentrations were determined via electroimmunoassay using a goat antirabbit apoA-I antibody raised in our laboratory by a modification of methods previously described. 17 …”
Section: Laboratory Measurementsmentioning
confidence: 99%
“…14 ApoA-I concentrations were determined via electroimmunoassay using a goat antirabbit apoA-I antibody raised in our laboratory by a modification of methods previously described. 17 …”
Section: Laboratory Measurementsmentioning
confidence: 99%
“…Results are also described for the peak flotation rate (S f ) of the LDL-mass distribution [12,13]. Plasma lipoprotein cholesterol concentrations were measured directly by the methods of the Lipid Research Clinics [14], plasma apolipoprotein B concentrations were assessed by radioimmunoassay [15], apolipoprotein A-I and A-II concentrations were measured by radialimmunodiffusion [16], and LCAT mass was measured by double antibody radioimmunoassay [17]. Assays of apolipoproteins and LCAT were made on all samples at the end of the study using plasmas that had been stored at −80°C.…”
Section: Subjects and Laboratory Measurementsmentioning
confidence: 99%
“…Furthermore, it has been reported that alcohol consumption, which is known to be associated with high HDL cholesterol (25 -27) and frequently with hypertriacylglycerolaemia (28, 29), mainly resulted in an enhanced level of HDL 3 mass without affecting HDL 2 mass (30). It has been shown that the apolipoprotein A-I/apolipoprotein A-II ratio in HDL/2 is higher than that in HDL 3 (31,32). Therefore, in individuals with heigh HDL cholesterol levels (which are associated with lower triacylglycerol) and a similarly high apolipoprotein A-I/apolipoprotein A-II ratio, a higher HDL2/HDL 3 ratio may exist in comparison to individuals with lower HDL cholesterol levels (which are associated with higher triacylglycerol) and a similarly low apolipoprotein A-I/apolipoprotein A-II ratio.…”
Section: Discussionmentioning
confidence: 99%